(untitled) (Research, Society and Development, 2025)
Objective: to identify the epidemiological profile of people affected by Covid-19 admitted to a reference hospital in the western border region of Rio Grande do Sul between 2020 and 2022. Method: Quantitative, cross-sectional and retrospective study, developed in a reference hospital for the care of patients with Covid-19 to the western-border region. The study population consisted of adult patients with Covid-19 admitted to the Clinical Unit-Covid, Intensive Care Unit-Covid (ICU-C), Pulmonary Ventilatory Support (PVS) and Emergency Room (ER) between March 2020 and August 2020. 2022. Results: Of the 1,811 patient records, 939 (51.85%) people are male, with a mean age of 56.85 years (SD±16.58). The period of hospitalization of people ranged from 5 to 15 days, with an average of 9.56 (SD±10.98). More than half (51.68%) of the sample required hospitalization of 7 days or less, 487 (26.89%) remained hospitalized for up to 7 days, and 263 (14.52%) people remained hospitalized in the hospital environment for up to 15 days. Conclusion: The municipality, the location of this study, presented a high number of notifications for Covid-19, although there may be a considerable number of underreporting, due to the fact that the disease is in many cases marked by asymptomatic conditions or with mild symptoms, which ends up not leading the individual to seek specialized health care and contributes to the spread of the disease.